Co-occurrence of opisthorchiasis and diabetes exacerbates morbidity of the hepatobiliary tract disease. - Apisit Chaidee; Sudarat Onsurathum; Kitti Intuyod; Patchareewan Pannangpetch; Chatlert Pongchaiyakul; Porntip Pinlaor; Chawalit Pairojkul; Wannaporn Ittiprasert; Christina J Cochran; Victoria H Mann; Paul J Brindley; Somchai Pinlaor (Public Library of Science (PLoS), 2018)
Complications arising from infection with the carcinogenic liver fluke Opisthorchis viverrini cause substantial morbidity and mortality in Thailand and adjacent lower Mekong countries. In parallel, the incidence rate of diabetes mellitus (DM) is increasing in this same region, and indeed worldwide. Many residents in opisthorchiasis-endemic regions also exhibit DM, but the hepatobiliary disease arising during the co-occurrence of these two conditions remains to be characterized. Here, the histopathological profile during co-occurrence of opisthorchiasis and DM was investigated in a rodent model of human opisthorchiasis in which diabetes was induced with streptozotocin. The effects of excretory/secretory products from the liver fluke, O. viverrini (OVES) on hepatocyte and cholangiocyte responses during hyperglycemic conditions also were monitored. Both the liver fluke-infected hamsters (OV group) and hamsters with DM lost weight compared to control hamsters. Weight loss was even more marked in the hamsters with both opisthorchiasis and DM (OD group). Hypertrophy of hepatocytes, altered biliary canaliculi, and biliary hyperplasia were more prominent in the OD group, compared with OV and DM groups. Profound oxidative DNA damage, evidenced by 8-oxo-2'-deoxyguanosine, proliferating cell nuclear antigen, and periductal fibrosis characterized the OD compared to OV and DM hamsters. Upregulation of expression of cytokines in response to infection and impairment of the pathway for insulin receptor substrate (IRS)/phosphatidylinositol-3-kinases (PI3K)/protein kinase B (AKT) signaling attended these changes. In vitro, OVES and glucose provoked time- and dose-dependent effects on the proliferation of both hepatocytes and cholangiocytes. In overview, the co-occurrence of opisthorchiasis and diabetes exacerbated pathophysiological damage to the hepatobiliary tract. We speculate that opisthorchiasis and diabetes together aggravate hepatobiliary pathogenesis through an IRS/PI3K/AKT-independent pathway.